2006
DOI: 10.1021/la061849h
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Pegylated Quantum Dots:  From a Composite Hexagonal Phase to Isolated Micelles

Abstract: We present a simple method based on the dispersion of fluorescent quantum dots (QD) into a liquid crystal phase that provides either nanostructured material or isolated QD micelles depending on water concentration. The liquid-crystal phase was obtained by using a gallate amphiphile with a poly(ethylene glycol) chain as the polar headgroup, named I. The hydration of QD/I mixtures resulted in the formation of a composite hexagonal phase identified by small-angle X-ray scattering and by polarized light and fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…Dynamic light scattering (DLS) showed that dispersions in chloroform Cd 0.1 Zn 0.9 Se and of Fe 3 O 4 , Fe 3 O 4 /Cd 0.1 Zn 0.9 Se@SiO 2 ( C ) NPs in water had size distributions centered at 25, 45 and 300 nm respectively (Figure S23, ESI). Although the DLS suggests a small amount of aggregation in solution, it is known that this technique yields higher diameters than those observed by TEM ,,. TEM and HRTEM demonstrate that the NPs have a core‐shell structure with a dark contrast metal core and a light contrast silica shell.…”
Section: Resultsmentioning
confidence: 94%
“…Dynamic light scattering (DLS) showed that dispersions in chloroform Cd 0.1 Zn 0.9 Se and of Fe 3 O 4 , Fe 3 O 4 /Cd 0.1 Zn 0.9 Se@SiO 2 ( C ) NPs in water had size distributions centered at 25, 45 and 300 nm respectively (Figure S23, ESI). Although the DLS suggests a small amount of aggregation in solution, it is known that this technique yields higher diameters than those observed by TEM ,,. TEM and HRTEM demonstrate that the NPs have a core‐shell structure with a dark contrast metal core and a light contrast silica shell.…”
Section: Resultsmentioning
confidence: 94%
“…In a typical example, extensive works have demonstrated that amphiphilic PEG polymers can well encapsulate QDs as the hydrophobic core and stabilize QDs in water [40,41,42,43]. The resulted biocompatible PEG/QDs have been shown to have the potential to detect and image biomolecules.…”
Section: How To Make Biocompatible Polymer/qds Hybrids?mentioning
confidence: 99%
“…Surface‐modified QDs with PEG are biocompatible both with living cells in culture (Ryman‐Rasmussen et al,2007) and whole animals. PEG polymer is an attractive corona‐forming candidate for micelles and QDs due to their physical, chemical, and biological properties as well as the availability of the material (Ballou et al,2007; Bentzen et al,2005; Boulmedais et al,2006; Yu et al,2006). Reports on the distribution and pharmacokinetic properties (Gao et al,2004; Kim et al,2004; So et al,2006) of cadmium selenide QDs show that these nanoparticles are sequestered in several organs after intravenous administration, but of particular note, they accumulate in lymph nodes (Frangioni et al,2007) and solid tumors (Ballou et al,2007).…”
Section: Qds For Imaging Single Cells and Animalsmentioning
confidence: 99%